2012
DOI: 10.3168/jds.2011-4391
|View full text |Cite
|
Sign up to set email alerts
|

Preweaning milk replacer intake and effects on long-term productivity of dairy calves

Abstract: The preweaning management of dairy calves over the last 30 yr has focused on mortality, early weaning, and rumen development. Recent studies suggest that nutrient intake from milk or milk replacer during the preweaning period alters the phenotypic expression for milk yield. The objective of this study was to investigate the relationship between nutrient intake from milk replacer and pre- and postweaning growth rate with lactation performance in the Cornell dairy herd and a commercial dairy farm. The analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
341
9
24

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(399 citation statements)
references
References 36 publications
25
341
9
24
Order By: Relevance
“…We have previously reported differences in ADG between 1 and 6 months of 0.5 to 1.0 kg/day between farms and of 0.45 to 1.15 kg/day between different heifers on the same farm (Brickell et al, 2009a). Similarly Soberon et al (2012) reported a range from 0.10 to 1.58 kg/day in dairy heifers over the pre-weaning period. Unfortunately few trials contain good growth rate data as relatively few farmers weigh their animals.…”
Section: Nutrition and Growth Ratementioning
confidence: 97%
See 2 more Smart Citations
“…We have previously reported differences in ADG between 1 and 6 months of 0.5 to 1.0 kg/day between farms and of 0.45 to 1.15 kg/day between different heifers on the same farm (Brickell et al, 2009a). Similarly Soberon et al (2012) reported a range from 0.10 to 1.58 kg/day in dairy heifers over the pre-weaning period. Unfortunately few trials contain good growth rate data as relatively few farmers weigh their animals.…”
Section: Nutrition and Growth Ratementioning
confidence: 97%
“…Another trial by Davis Rincker et al (2011) found that pre-weaned heifers provided with a higher energy and protein diet did not alter their energy-corrected, ageuncorrected 305-day milk yield in comparison with those fed a conventional diet (averaging 10 069 and 9778 kg, respectively) although this difference became significant when the genetic values of the heifers were taken into account. Similarly, Soberon et al (2012) reported that for every 1 kg increase in ADG during the pre-weaning period, first lactation milk yield increased by 850 and 1113 kg in two different herds studied, showing a consistent positive effect of good early growth on subsequent milk production. This was supported by other studies showing that calves fed more milk (Shamay et al, 2005) or with a higher ADG from solid feed in their first 2 months (Bach and Ahedo, 2008) produced more first lactation milk.…”
Section: Milk Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soberon et al (2012) described a mean of 0.82 ± 0.18 kg/day of pre-weaning growth rates, with a range from 0.10 to 1.58 kg/day from the Cornell herd. Also, in that study a commercial American dairy farm showed a mean of 0.66 ± 0.11 kg/day, with a range from 0.32 to 1.27 kg/day.…”
Section: Datamentioning
confidence: 99%
“…It regulates production systems' feasibility, e.g., herd's renewal. More recently, it has been shown that fostering rapid growth early in life may have positive consequences on future milk performance (SOBERON et al, 2012) and survivability to second lactation. To obtain good results for dairy calf performance after weaning, animal consumption of adequate quantities of solid food is imperative before complete milk withdrawal (MILLER-CUSHON et al, 2013).…”
Section: Introductionmentioning
confidence: 99%